Fibers development in a dioecious hemp cultivar: the role of plant sex and cultivation conditions. (2nd January 2023) - Cerri, Martina; Reale, Lara; Roscini, Francesca; Fornaciari da Passano, Marco; Orlandi, Fabio
Abstract: Hemp ( Cannabis sativa ) is a well-known crop with a great potential to produce fibers without being excessively water and nutrient demanding. Moreover, hemp can be considered a viable and sustainable alternative to reach a cleaner production in the garment industry. Accurate information on fiber traits will enhance the exploitation of hemp in textile and biofuel industry. The aim of this work was to investigate the cyto-histological characteristics of hemp primary and secondary fibers through semi-thin sections and a light microscopy approach. To this purpose, we cultivated in open field a dioecious hemp variety under two different sowing densities and two different fertilization regimes. We confirmed the prominent role of sex in influencing all the analyzed traits; moreover, we found the possibility to mitigate it by changing the sowing density and the fertilization regime. In particular, the cell wall thickening in primary fibers was reduced in female plants by high fertilization. In male plants, combining high fertilization and low density, secondary fibers development is deeply increased. Cell area, in both plant sexes, was reduced by high fertilization. Operating on these simple agronomic aspects could thus result in the desired amount of fibers/lignin, depending on the final purpose of hemp cultivation.